PENGENDALIAN KONVERSI LAHAN SAWAH MENJADI INDUSTRI DAN PERUMAHAN DI KABUPATEN SUKOHARJO TAHUN 2010-2013 - Nur Isnaeni Ari Wardani; Muhammad Adnan; Wiwik Widayati (Journal of Politic and Government Studies, 2015)
This research aims to find out how Government control of the transfer function of the Sukoharjo Regency farmland to non agricultural usage especially for housing and industry. As well as to know the business and political conflicts of interest involved in control by the local authorities to issue the land over the function. Sukoharjo Regency is a Regency in Central Java that included into the district who have ample rice field acreage. Conversion issues or over the function of agricultural land into industrial zones and housing continues to this day. Judging from the extensive rice according to the type of irrigation of district and of the respective districts, from 2010-2013 has decreased the number of vast rice fields. The decrease in the number of extensive rice due to the high agricultural land use changes into residential and industrial land. In the Regulatory Area of the Spatial Plan and The No. 14 in 2011 is explained in article 5 paragraph 3 letter b which prevents over land irrigated rice fields on the function of the technical. The problem is how the commitment of local governments in controlling land conversion, and the problem is a clash of business interests and political relations between local governments as the giver of the permit location with investors as the applicant permission to perform particular neighborhoods and industrial development carried out above farmland.In this study, the researchers used a qualitative approach that will generate descriptive data. to get the appropriate data sources for research purposes so researchers conduct interviews conducted with the Department of agriculture Production, Kasi Kasubag Land The Government Secretariat area, head of spatial planning of LEGISLATIVE members of the DPU, Sukoharjo Regency, Investor/Developer/Entrepreneur housing. The results showed that local governments are already working to maintain sustainable agricultural land protection, but because of the many needs and demands from the public to the needs of the settlements and industry, as well as a petition from a developer or investor, then the local Government finally gave permission to the location of the development on agricultural land. The involvement of business and political relationships that occur between local governments and the investor appears due to the cooperation of the two parties. On the other hand an investor wants to develop land for settlements and industry, whereas the local governments need to improve regional development.